Kerr-effect induced correlations of optical fiber solitons and the impact of phase control - Leuchs, Gerd; Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Heersink, Joel; Korolkova, Natalia (Frontiers in Optics 2003, 2003)
Experiments are reported in which the quantum properties of intense optical pulses at 1.5 micrometer are controlled via their non-linear interaction with the optical fiber. Intense light pulses may exhibit non-classical features such as entanglement with application in quantum communication. The role of phase control will be discussed.<br